2015
DOI: 10.1111/apm.12389
|View full text |Cite
|
Sign up to set email alerts
|

Profiling peripheral microRNAs in obesity and type 2 diabetes mellitus

Abstract: Mechanisms of type 2 diabetes mellitus (T2DM) remain elusive, in which obesity (OB) is considered as one of the major risk factors for the disease. A microRNA (miRNA) is a small non-coding RNA molecule functioning in RNA silencing and post-transcriptional regulation of gene expression. It has been demonstrated that some miRNAs can exist in serum stably and is closely related to various diseases. The goal of our study was to identify whether the deregulation of serum miRNAs was associated with T2DM and obesity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 23 publications
0
31
0
3
Order By: Relevance
“…Previous studies have shown that endogenous exosome production and content are affected by disease states in humans (31, 32) and can be used as biomarkers for diseases such as obesity and type 2 diabetes (33). However, it is unclear from these studies whether exosomes are playing a role in disease or if they are mere byproducts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that endogenous exosome production and content are affected by disease states in humans (31, 32) and can be used as biomarkers for diseases such as obesity and type 2 diabetes (33). However, it is unclear from these studies whether exosomes are playing a role in disease or if they are mere byproducts.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some miRNAs have been identified as potential biomarkers for distinguishing obesity from T2DM [49, 50]. In an analysis of patient sera, Wu et al .…”
Section: Mirnas As Potential Biomarkers Of Metabolic Disordersmentioning
confidence: 99%
“…found the expression of the deregulated miRNAs, including miR-152, miR-17, miR-138, miR-593, miR-150, miR-205, miR-376a, miR-432-5p and miR-500a, to differ between a group of 25 healthy control subjects and groups of 25 patients with T2DM, 25 obese (OB) and 25 OB + T2DM patients. An analysis of the area under the curve (AUC) values based on receiver operating characteristic curves for each miRNA revealed that miR-152, miR-17, miR-593 and miR-138 alone can be used to distinguish patients with OB from those with T2DM, OB + T2DM or healthy subjects [49]. Similarly, Pescador et al .…”
Section: Mirnas As Potential Biomarkers Of Metabolic Disordersmentioning
confidence: 99%
“…Transforming growth factor β1 (TGF‐β1) is the most important fibrotic factor known to be involved in the regulation of glomerular interstitial sediment synthesis and decomposition, cell growth, and formation of extracellular matrix . Increased expression of TGF‐β1 and activation of its downstream signaling pathway may be associated with fibrosis caused by various factors such as inflammatory factors, angiotensin II, and ischemia.…”
Section: Introductionmentioning
confidence: 99%